Review of the genus Hierodula Burmeister (Mantodea: Mantidae) in Iran - Mirzaee, Zohreh; Wiemers, Martin; Schmitt, Thomas; Govorov, Valeriy; Shcherbakov, Evgeny (Frontiers in Insect Science, 2026)
IntroductionHierodula is a morphologically conservative mantid genus with a complex taxonomic history and several problematic species-level concepts across its native and invaded ranges. In Iran, four nominal Hierodula species have historically been reported (H. macrostigmata, H. tenuidentata, H. transcaucasica, and “H. trimacula”), but their validity and distributions have remained uncertain due to overlapping diagnostic characters and limited molecular data. This study addresses these issues by reassessing all available Iranian material within an integrative framework.MethodsThe revision combines: Morphological examination of type and non-type material from Iran, India, Pakistan, and Oman, including detailed study of external characters and male genitalia. Mitochondrial COI barcoding of Hierodula specimens from multiple Iranian provinces and Pakistan, analyzed with Bayesian inference, maximum likelihood, and model-based genetic distance estimation. Compilation and critical validation of distributional data from museum collections, literature, and iNaturalist records, followed by mapping in QGIS.ResultsMorphological comparisons show that the holotype of H. macrostigmata and recently collected southern Iranian specimens are indistinguishable from H. coarctata in forewing stigma, pronotal shape, and male genitalia, supporting their synonymy. COI phylogenies and TN93 genetic distances recover two deeply divergent, well-supported clades corresponding to H. coarctata and the H. tenuidentata complex, with minimal intraspecific divergence and no separation between Iranian “H. macrostigmata” and Indian/Pakistani H. coarctata. Re-examination of specimens and literature demonstrates that records of “Hierodula/Sphodromantis trimacula” from Iran lack verifiable material, while male genital characters place the species unambiguously in Sphodromantis and confirm its absence from the Iranian fauna.DiscussionThe integrative evidence indicates that only H. coarctata and H. tenuidentata are currently valid Hierodula species in Iran, with H. macrostigmata as a junior synonym of H. coarctata and previous Iranian reports of S. trimacula rejected. The clear molecular separation between H. coarctata and the H. tenuidentata complex, combined with broad morphological variability in traits such as forefemoral spine coloration, underscores the need to abandon historically overemphasized colour characters and highlights the utility of COI barcoding in resolving conservative mantid lineages. Remaining uncertainty regarding the status of H. transcaucasica versus H. tenuidentata at a broader Eurasian scale calls for a forthcoming multi-locus, range-wide revision to formally resolve their taxonomy.